2017
DOI: 10.1111/pim.12451
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine potential of HLA‐A2 epitopes from Leishmania Cysteine Protease Type III (CPC)

Abstract: Although the precise host-defence mechanisms are not completely understood, T-cell-mediated immune responses are believed to play a pivotal role in controlling parasite infection. In this study, the potential HLA*A2 restricted peptides were predicted and the ability of peptides to bind HLA-A*02 was confirmed by a MHC stabilization assay. Two of the peptides tested stabilized HLA-A*02: (a) LLATTVSGL (P1) and (b) LMTNGPLEV (P3). The potential of the peptides to generate protective immune response was evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Most of the studies have focused on the identification of HLA-I epitopes [74][75][76][77][78][79][80] but only a few have been conducted to predict HLA-II [81][82][83] or a combination of both HLA-I and -II epitopes [23,84,85]. In this study, we described peptides containing multiple HLA-I and -II epitopes that would induce both CD8+ and CD4+ T cell responses, crucial for protection.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies have focused on the identification of HLA-I epitopes [74][75][76][77][78][79][80] but only a few have been conducted to predict HLA-II [81][82][83] or a combination of both HLA-I and -II epitopes [23,84,85]. In this study, we described peptides containing multiple HLA-I and -II epitopes that would induce both CD8+ and CD4+ T cell responses, crucial for protection.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Some studies have shown significant levels of IFN-γ and low levels of IL-10 in response to HLA-I or HLA-II restricted epitopes derived from different Leishmania proteins, used alone or as pools, in cured CL or visceral leishmaniasis (VL) individuals [75,77,78,83]. However, only a few studies have focused on the identification of both HLA-I and -II restricted peptides.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant potentiality of individual P1 or P3 to generate protective immune response (CD8 + T-cell proliferation) was observed in treated VL patients compared to healthy controls. Development of DNA vaccine against VL employing combined P1 and P3 was recommended [80] .…”
Section: Leishmania Caths As Vaccine Candidatesmentioning
confidence: 99%
“…It leads to the creation of a plethora of antigens changing constantly on the surface of viral glycoprotein. Its structural features disguise conserved receptor-binding sites from the immune system, and potential epitopes are shielded from antibodies by the presence of carbohydrate moieties (Stein 1990, Dikhit, Amit et al 2017. The rapid advance of computation work and Bioinformatics approaches has increased our ability to understand HIV-1 structure and antibody approach towards immunogenic design.…”
Section: Introduction:-mentioning
confidence: 99%